THE PESSIMISTIC INDUCTION AND THE GOLDEN RULE. - Seungbae Park (Problems / Problemos, 2018)
Nickles advocates scientific antirealism by appealing to the illusion hypothesis, the pessimistic induction over scientific theories, Darwin's evolutionary theory, and the problem of underdetermination. I object that both the illusion hypothesis and evolutionary theory clash with the pessimistic induction and with the problem of underdetermination. I also argue that Nickles's positive philosophical theories are subject to Park's pessimistic induction over antirealists. Finally, I apply the Golden Rule to antirealists, viz., if antirealists do not want scientists to run the pessimistic induction over antirealists, antirealists ought not to run the pessimistic induction over scientific theories.